An Investigation of ZZ/ZW and XX/XY Sex Determination Systems in North African Catfish (Clarias gariepinus, Burchell, 1822) - Nguyen, Dung Ho My; Panthum, Thitipong; Ponjarat, Jatupong; Laopichienpong, Nararat; Kraichak, Ekaphan; Singchat, Worapong; Ahmad, Syed Farhan; Muangmai, Narongrit; Peyachoknagul, Surin; Na-Nakorn, Uthairat; Srikulnath, Kornsorn (Frontiers in Genetics, 2021)
An investigation of sex-specific loci may provide important insights into fish sex determination strategies. This may be useful for biotechnological purposes, for example, to produce all-male or all-female fish for commercial breeding. The North African catfish species, Clarias gariepinus, has been widely adopted for aquaculture because its superior growth and disease resistance render the species suitable for hybridization with other catfish to improve the productivity and quality of fish meat. This species has either a ZZ/ZW or XX/XY sex determination system. Here, we investigate and characterize these systems using high-throughput genome complexity reduction sequencing as Diversity Arrays Technology. This approach was effective in identifying moderately sex-linked loci with both single-nucleotide polymorphisms (SNPs) and restriction fragment presence/absence (PA) markers in 30 perfectly sexed individuals of C. gariepinus. However, SNPs based markers were not found in this study. In total, 41 loci met the criteria for being moderately male-linked (with male vs. female ratios 80:20 and 70:30), while 25 loci were found to be moderately linked to female sex. No strictly male- or female-linked loci were detected. Seven moderately male-linked loci were partially homologous to some classes of transposable elements and three moderately male-linked loci were partially homologous to functional genes. Our data showed that the male heterogametic XX/XY sex determination system should co-exist with the ZZ/ZW system in C. gariepinus. Our finding of the co-existence of XX/XY and ZZ/ZW systems can be applied to benefit commercial breeding of this species in Thailand. This approach using moderately sex-linked loci provides a solid baseline for revealing sex determination mechanisms and identify potential sex determination regions in catfish, allowing further investigation of genetic improvements in breeding programs.